MANTRA PAMBARASIAH DIRI DALAM MASYARAKAT KELURAHAN KORONG GADANGKECAMATAN KURANJI KOTA PADANG - Ramadhani, Deby Tri; Nasution, Bakhtaruddin; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2013)
This article aims to (a) describe the structure of mantra â€œpambarasiah diriâ€œ (b) supporting aspects incantations mantra â€œpambarasiah diriâ€, (c) the process of inheritance mantra â€œpambarasiah diriâ€ in the Kelurahan Korong Gadang Kecamatan Kuranji Kota Padang. Data collected by interview using dictation techniques. The study's findings are mantra â€œpambarasiah diriâ€ structure it self consists of opening, contents and cover. Supporting aspects incantations consists of (1) time: free, there is no provision read in the mantra, (2) where: there is that does not require a special place, and there can not read the mantra but at home, (3) events: when the shaman and the patient has to deal or face to face, (4) actors: shaman himself, (5) equipment: water bottle, al-quran, coconut oil, flowers seven-way, (6) clothing: depends shaman, there is a free and anyone cloth gloves and clothes in white, and (7) rendition mantra: mantra was read slowly and with concentration. While the process of succession mantra or mantra intended for the recipient or beneficiary. Each shaman has individual requirements, there are bathing in the river, paraded or meditate.